Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae) - Wesener, Thomas (Zootaxa, 2016)
Sphaeropoeus hercules Brandt, 1833, the type species of one of the oldest genus names in Sphaerotheriida, is redescribed for the first time based on its fragmented type specimen. While damaged, the specimen shows characters clearly different from other, diverse and similar genera of the family Zephroniidae, such as Zephronia Gray, 1832 and Castanotherium Pocock, 1895. S. hercules has a record number of >180 apical cones on the antennae, more than any other millipede. The species, together with another species of the genus Castanotherium, C. insigne (Brandt, 1833) is added to an existing character matrix currently comprising 100 characters and 46 species. A second never-revised species of Sphaeropoeus, S. variegatus Pocock, 1895, is also redescribed based on type material. The latter seems to belong to the genus Sphaeropoeus, but its provenance remains currently unknown. S. variegatus could not be added to the character matrix because several important characters could not be studied. The phylogenetic analysis resolved the position of Sphaeropoeus in the Zephroniidae, but gave no resolution of the intrafamiliar relationships of the family’s numerous genera.